2021
DOI: 10.1186/s13568-021-01208-6
|View full text |Cite
|
Sign up to set email alerts
|

Design of a novel antimicrobial peptide 1018M targeted ppGpp to inhibit MRSA biofilm formation

Abstract: Methicillin-resistant staphylococcus aureus (MRSA) and its biofilm infection were considered as one of the main international health issues. There are still many challenges for treatment using traditional antibiotics. In this study, a mutant peptide of innate defense regulator (IDR-)1018 named 1018M was designed based on molecular docking and amino acid substitution technology. The antibacterial/biofilm activity and mechanisms against MRSA of 1018M were investigated for the first time. The minimum inhibitory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
1
10
1
Order By: Relevance
“…In our study, the transcriptional levels of genes (agrA, sigB, and lrgB) in CTPstreated biofilms were not significantly different, which might prove that the antibiofilm activity of CTPs mainly relied on membrane destruction, instead of the regulation of gene expression (Figure 12). However, these results may differ from Jiale's report that AMP 1018 M could display both disruption of the cell membrane and modulation of biofilmassociated gene expression, which might be due to the target of 1018 M function being ppGpp, a stringent response signaling molecule that regulates the expression of many biofilm-formation-relevant genes [49]. As shown in Figure 14, we speculated on the mechanisms of antibacterial and antibiofilm effects of CTPs against S. aureus ATCC 43300 in the hypothesized model.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In our study, the transcriptional levels of genes (agrA, sigB, and lrgB) in CTPstreated biofilms were not significantly different, which might prove that the antibiofilm activity of CTPs mainly relied on membrane destruction, instead of the regulation of gene expression (Figure 12). However, these results may differ from Jiale's report that AMP 1018 M could display both disruption of the cell membrane and modulation of biofilmassociated gene expression, which might be due to the target of 1018 M function being ppGpp, a stringent response signaling molecule that regulates the expression of many biofilm-formation-relevant genes [49]. As shown in Figure 14, we speculated on the mechanisms of antibacterial and antibiofilm effects of CTPs against S. aureus ATCC 43300 in the hypothesized model.…”
Section: Discussioncontrasting
confidence: 95%
“…All of the CTPs exhibited significant antibiofilm activity and could effectively inhibit biofilm formation of most tested S. aureus strains at sublethal concentrations (1 × MIC), as detected using the crystal violet method (Figure 9). This was consistent with other reports, which suggest that membrane-penetrated peptides may also block the formation of pathogen biofilms [49,50]. C-terminal amidation of the peptides has been reported to enhance its antibiofilm activity [51].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1018M inhibited biofilm formation, but IDR-1018 did not affect biofilm formation. 1018M's hydrophobicity is significantly less than IDR-1018, and its hydrophobic ratio was 25% less than IDR-1018 [52]. In Fig.…”
Section: Fig 8 Comparsion Of Physicochemical Properties Between Abfs ...mentioning
confidence: 86%
“…The morphological parameters of the cell were changed, and the metabolic activity was inhibited at a very high level. When studying the opportunities for the achievement of the desired effect in newly arisen infections through a decrease in the concentration of the peptide fraction but with an increase in the exposition time, we found that the 10% peptide fraction led to the achievement of the desired effectdamage to the structures and functions of the bacteria [65][66][67]. This led to a decrease in the fluorescence as a result of the blocking of the oxide reductase apparatus of the cells, and accumulation of degenerative bacterial cells, which were shortened and round, and had highly damaged surfaces.…”
Section: Discussionmentioning
confidence: 99%